Comparative genomic analysis identifies an evolutionary shift of vomeronasal receptor gene repertoires in the vertebrate transition from water to land - Shi, Peng; Zhang, Jianzhi (Genome Research, 2007)
Two evolutionarily unrelated superfamilies of G-protein coupled receptors, V1Rs and V2Rs, bind pheromones and “ordinary” odorants to initiate vomeronasal chemical senses in vertebrates, which play important roles in many aspects of an organism’s daily life such as mating, territoriality, and foraging. To study the macroevolution of vomeronasal sensitivity, we identified all V1R and V2R genes from the genome sequences of 11 vertebrates. Our analysis suggests the presence of multiple V1R and V2R genes in the common ancestor of teleost fish and tetrapods and reveals an exceptionally large among-species variation in the sizes of these gene repertoires. Interestingly, the ratio of the number of intact V1R genes to that of V2R genes increased by ∼50-fold as land vertebrates evolved from aquatic vertebrates. A similar increase was found for the ratio of the number of class II odorant receptor (OR) genes to that of class I genes, but not in other vertebrate gene families. Because V1Rs and class II ORs have been suggested to bind to small airborne chemicals, whereas V2Rs and class I ORs recognize water-soluble molecules, these increases reflect a rare case of adaptation to terrestrial life at the gene family level. Several gene families known to function in concert with V2Rs in the mouse are absent outside rodents, indicating rapid changes of interactions between vomeronasal receptors and their molecular partners. Taken together, our results demonstrate the exceptional evolutionary fluidity of vomeronasal receptors, making them excellent targets for studying the molecular basis of physiological and behavioral diversity and adaptation.
10.1101/gr.6040007